Letter - Winstanley, E.
030-0202-001 Mr. Parkin Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. Our reference EXPORT ST/HP. 345 Your reference 10th February, 1938. The Trades Union Congress General Council, Transport House, Smith Square, LONDON. Dear Sirs, We have pleasure in attaching hereto credit note amounting to £5.11.5. in respect of 5 bags Sugar short shipped from the s.s. PLOVER to Barcelona. Yours faithfully, E. Winstanley Export Department. 292/946/30/202